x=-5 and x=13
Step-by-step explanation:
Given equation is:
[tex]x^2-8x-65=0[/tex]
Adding 65 to both sides
[tex]x^2-8x-65+65=0+65\\x^2-8x=65[/tex]
Now to decide what to add
[tex]8x = 2ab\\8x=2.x.b\\\frac{8x}{2x} = b\\b=4[/tex]
So we will add (4)^2 to both sides
[tex]x^2-8x+(4)^2=65+(4)^2\\Using\ formula: (a^2-2ab+b^2)=(a-b)^2\\(x-4)^2=65+16\\(x-4)^2=81Taking\ square\ root\ on\ both\ sides\\\sqrt{(x-4)^2}=\sqrt{81}\\x-4=-9\ \ \ \ and\ x-4=9\\x=-9+4\ \ \ \ and\ \ \ x=9+4\\x=-5,\ x=13[/tex]
So the solution is:
x=-5 and x=13
Keywords: Completing Square, Variables
Learn more about quadratic equations at:
#LearnwithBrainly